2008
DOI: 10.1071/en08015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the adsorption mechanism of imidazolium-type ionic liquids onto kaolinite: implications for their fate and transport in the soil environment

Abstract: Environmental context. The present paper looks at the possible spreading of a new class of chemicals, namely, ionic liquids in soils. These ionic liquids have gained increasing attention, and their environmental impact and fate needs to be determined before accidental release. The paper specifically focusses on the adhesion mechanisms of these chemicals onto a type of clay, kaolinite. It was found that a multilayer adhesion mechanism occurs. Sorption of ionic liquids on kaolinite indicates that these chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Although the values of E found in the current study were within the energy range of physical adsorption, the following results indicated that the cation exchange was the main mechanism controlling adsorption and desorption of Na + in the control soil and amended soil. Mrozik et al (2008) and Caliskan et al (2011) indicated that adsorption energy values obtained were below values of a typical chemisorption process. However, based on the kinetic study, they concluded that the adsorption mechanism was a combination of electrostatic interaction and physical sorption.…”
Section: Na + Exchange Isotherms and Fitting Empirical Modelsmentioning
confidence: 82%
“…Although the values of E found in the current study were within the energy range of physical adsorption, the following results indicated that the cation exchange was the main mechanism controlling adsorption and desorption of Na + in the control soil and amended soil. Mrozik et al (2008) and Caliskan et al (2011) indicated that adsorption energy values obtained were below values of a typical chemisorption process. However, based on the kinetic study, they concluded that the adsorption mechanism was a combination of electrostatic interaction and physical sorption.…”
Section: Na + Exchange Isotherms and Fitting Empirical Modelsmentioning
confidence: 82%
“…The sorption isotherms and equilibrium sorption coefficients of selected imidazolium IL cations with different alkyl side-chain lengths have been determined and compared for several types of soils, kaolinite, and one sediment differing in their physicochemical properties (Mrozik et al 2008;Stepnowski 2005a;Stepnowski et al 2007). All the compounds were found to be strongly sorbed onto these substrates, and the longer the alkyl chain, the greater the sorption capacity.…”
mentioning
confidence: 99%
“…values obtained in the experiments with different concentrations. Since physicochemical sorption is the most probable mechanism in this case, the results reflect the concentration-dependent mechanism of IL retention, typical of mineral surfaces (Mrozik et al 2008).…”
Section: Resultsmentioning
confidence: 96%